Text mining for U.S. pension de-risking analysis - Limin Zhang; Ruilin Tian; Jun Chen (Risks, 2022)
In the past 30 years, as sponsors of defined benefit (DB) pension plans were facing more severe underfunding challenges, pension de-risking strategies have become prevalent for firms with DB plans to reduce pension-related risks. However, it remains unclear how pension de-risking activities affect firms' performance, partially due to the lack of de-risking data. In this study, we develop a multi-phase methodology to build a de-risking database for the purpose of investigating impacts of firms' pension risk transfer activities. We extract company filings between 1993 and 2018 from the SEC EDGAR database to identify different "de-risking" strategies that US-based companies have used. A combination of text mining, machine learning, and natural language processing methods is applied to the textual data for automated identification and classification of de-risking strategies. The contribution of this study is three-fold: (1) the design of a multi-phase methodology that identifies and extracts hidden information from a large amount of textual data; (2) the development of a comprehensive database for pension de-risking activities of US-based companies; and (3) valuable insights to companies with DB plans, pensioners, and practitioners in pension de-risking markets through empirical analysis.
Keywords: 330; classification; machine learning; natural language processing; pension de-risking; SEC EDGAR; supervised learning; text mining